Rasio Likuiditas dan Profitabilitas Dalam Mengukur Kinerja Keuangan Periode 2020-2022 - A, Yusril Izhaq Mahendra; Machmud, Mulyana; Hasan, Hamida; Anggerwati, A. Indah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This research aims to find out how the financial performance of PDAM Sidenreng Rappang Regency is measured using Liquidity and Profitability Ratios.The analytical method used in this research is the financial ratio analysis method. The financial reports are then analyzed using liquidity ratio (Current Ratio, Quick Ratio, Cash Ratio, Cash Turn Over, Inventory to Net Working Capital) and profitability ratios (Net Profit Margin, Retrun on investment, and Return on Equity)These results show that: for liquidity ratios, namely Current Ratio, from 2020 to 2022 with an average of 6.63 times, it is in accordance with industry standards, Quick Rati, from 2020 - 2022 with an average of 6.30 times is in accordance with industry standards, Cash Ratio, in 2020 and 2022 is in line with industry standards with an average of 81.78%, while 2021 does not yet meet industry standards, Cash Turn Over, from 2020 - 2022 with an average of 292% is in line with industry standards, and Inventory to Net Working Capital with an average of an average of 5.75% does not meet industry standards. For the profitability ratio, namely Net Profit Margin, from 2020 - 2022 the average (23.44%) does not meet established industry standards. Return on investment, from 2020 - 2022 with an average of (8.57%) does not comply with established industry standards, and Return On Equity, from 2020 - 2022 with an average of (8.84%) does not comply with established industry standards. has been set.